2018
DOI: 10.1186/s12885-018-4396-4
|View full text |Cite
|
Sign up to set email alerts
|

First case of AML with rare chromosome translocations: a case report of twins

Abstract: BackgroundLeukemia is different from solid tumor by harboring genetic rearrangements that predict prognosis and guide treatment strategy. PML-RARA, RUNX1-RUNX1T1, and KMT2A-rearrangement are common genetic rearrangements that drive the development of acute myeloid leukemia (AML). By contrast, rare genetic rearrangements may also contribute to leukemogenesis but are less summarized.Case presentationHere we reported rare fusion genes ZNF717-ZNF37A, ZNF273-DGKA, and ZDHHC2-TTTY15 in a 47-year-old AML-M4 patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…Some authors have reported that ubiquitin specific peptidase 9, Y-linked (USP9Y)– TTTY15 is expressed in both tumor and nonmalignant samples and can be used to predict the outcome of a prostate biopsy [17,18,27]. The TTTY15 gene can get fused to >zinc finger DHHC-type containing 2 (ZDHHC2– TTTY15 ), and this fusion is found in patients with acute myeloid leukemia [28]. In addition to forming fusion genes, TTTY15 (its product) can protect cardiomyocytes from hypoxia-induced cell injury by targeting miR-455-5p and thus regulating Jun dimerization protein 2 (JDP2) expression [29].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported that ubiquitin specific peptidase 9, Y-linked (USP9Y)– TTTY15 is expressed in both tumor and nonmalignant samples and can be used to predict the outcome of a prostate biopsy [17,18,27]. The TTTY15 gene can get fused to >zinc finger DHHC-type containing 2 (ZDHHC2– TTTY15 ), and this fusion is found in patients with acute myeloid leukemia [28]. In addition to forming fusion genes, TTTY15 (its product) can protect cardiomyocytes from hypoxia-induced cell injury by targeting miR-455-5p and thus regulating Jun dimerization protein 2 (JDP2) expression [29].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer links is defined broadly as any literature link between a ZDHHC-family member and a particular cancer, including large-scale and small-scale experimental studies, animal and cell culture studies, and clinical studies, whether functional or correlative. References: ZDHHC2[70,129,130], ZDHHC3[131][132][133], ZDHHC5[87], ZDHHC7[47,134], ZDHHC9[89,92,135,136], ZDHHC11[77,78,137,138], ZDHHC13[49,73], ZDHHC14[82][83][84][85], ZDHHC20[81], ZDHHC23[139]. HPA, Human Protein Atlas (www.proteinatlas.org/).…”
mentioning
confidence: 99%
“…A novel AML subtype (cluster C5) is characterized by enhancer deletion of ZNF37A in 16 patients ( Figure S17A). ZNF37A is involved in fusion events in breast cancer (57) and adult AML (58). Notably, AML patients with ZNF37A enhancer deletion have lower ZNF37A expression and shorter time to relapse ( Figure S17B, C), suggesting the prognosis significance of this noncoding mutation.…”
Section: Integrated Mutation Profiles Suggest Novel Disease Subtypesmentioning
confidence: 97%